Identificación de plagas en zea mays l. amiláceo en Santa Cruz de Chuca, Santiago de Chuco – La Libertad - Castillo Burgos, Sandra Isela (2017)
El this research work was performed in Santa Cruz de Chuca Province of Santiago de Chuco, Department of La Libertad, having as general objective to identify the pests on Zea mays L. amiláceo in the area of San Isidro.The type of research was descriptive, the methodology used For obtaining data was the visits to the three fields of the crop producer's most representative during the whole vegetative period of the crop to maturation to take samples, photographs, and survey application. The insects that were found within the three fields of growing corn were: Agrotis ípsilon (earthworm), Spodoptera frugiperda L. (cogollero), Acheta domesticus L. (Cricket), Thrips tabaci (Thrips), Epitrix hirtipennis Melsheimer (flea yellowtail), Rhopalosiphum maidis L. (Aphid), Mizus persicae Sulzer (Aphids), Peregrinus maidis L. (Cigarrita brown), Dalbulus maidis L. (Cigarrita cream), Diabrotica viridula L. (Diabrótica), p Genus diabrotica (Diabrótica), Heliothis zea L. (Worm mazorquero), Euxesta stigmatias Loew (Fly on the cob), Pagiocerus frontalis Fabr. (Weevil maize) in Santa Cruz de Chuca, Santiago de Chuco – La Libertad. The insects of greatest importance for the cultivation of corn were: Agrotis ípsilon (earthworm), Spodoptera frugiperda L. (cogollero), Heliothis zea L. (Worm mazorquero), Pagiocerus frontalis Fabr. (Weevils of maize).